Vaccination Perceptions and Barriers of School Employees: A Pilot Study. (August 2013) - Luthy, Karlen E.; Houle, Kim; Beckstrand, Renea L.; Macintosh, Janelle; Lakin, Richard G.
Schools are where vaccine-preventable diseases can spread. Vaccination of school children has been studied; however, data are lacking on the vaccination status, perceptions, and barriers to vaccination for school employees. We surveyed school employees' vaccination perceptions, awareness of current vaccination status, and potential barriers to vaccinations. Adult vaccination knowledge is lacking in the school employee population. School employees were unaware of their vaccination status for diseases such as measles and pertussis. Most subjects believed vaccinations were safe and effective, although they believed vaccinations were more important for children than adults. Many believed vaccine mandates should exist for school employees. Knowledge gaps regarding adult vaccines can be positively influenced by school nurses. Gaps may be especially important to bridge regarding adults working in the school setting, an environment ideal for the spreading of communicable diseases.